Comparison of Neonatal Outcome of Late Pre-Term Neonates Associated with and Without Intrauterine Growth Retardation - Shahid, Hassnain; Ikram, Farooq; Saleem, Maryam; Zulqarnain, Hafiz; Zaman, Saeed; Atif Naseem Abbasi (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the neonatal outcome of late pre-term neonates with and without intrauterine growth retardation at a nursing intensive care unit of our hospitalStudy Design: Comparative cross-sectional study.Place and Duration of Study: Pak Emirates Military Hospital ,Rawalpindi Pakistan, from Jun 2021 to Jan 2022.Methodology: Patients were divided into two groups for comparison, late pre-term neonates with and without intrauterine growth retardation. Intrauterine growth retardation was assessed via ultrasound examination at >29 and